PENGARUH PENGALAMAN, PENGETAHUAN, AUDIT TENURE DAN PEER REVIEW TERHADAP KUALITAS AUDIT (Studi Empiris Pada Kantor Akuntan Publik Di Pekanbaru, Batam, Padang dan Medan) - Nova Wulandari; Rasuli '; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Audit is a process to reduce the information contained in consistencies between managers and share holders. So the company should be more critical in choosing Public Accounting Firm to the financial statements audited by a public accountants a report that is free from material misstatement, be credible. There fore, we need a professional services independent and objective public accountants to assess the fairness of the financial statements presented by management. This study aimed to examine the effect of experience, knowledge, audit tenure and peer review of audit quality in the public accounting firm in Pekanbaru, Batam, Padang and Medan. The sampling technique using purposive sampling. Data collection methods conducted by using a questionnaire. The data collected will be analyzed using multiple linear regression. The results showed that the experience, knowledge, peer reviewed significant effect on audit quality. While no effect exhibited significantly audit tenure on audit quality produced by a public accountant. The amount of donations influence the experience, knowledge, audit tenure and peer review of audit quality by 59%.Keywords: Experience, Knowledge, Audit Tenure, Peer Review and Quality Audit